Learning Research Methods of Based Problem Solving Reviewed from Cognitive and Critical Thinking Ability - Julia Maulina; Susilo Sudarman (Pascasarjana Universitas Negeri Medan, 2016)
Abstract. This study shows the effect of the method of problem solving on cognitive abilities and critical thinking skills in making proposals of educational research articles. This study used an experimental method, which was implemented in January 2015 until July 2015. The sample consisted of one class of a study that students of Chemical Education FKIP UISU TA. 2014/2015. The results were obtained using two test method is to test the cognitive domain that is a multiple choice test and critical thinking skills in the form of making a research proposal. From the results of the analysis, there is the influence of problem solving methods to the learning outcomes of students' critical thinking and student learning outcomes multiple-choice test on the results of student learning materials Research Methods. No influence student results test multiple-choice to the learning outcomes of students' critical thinking on the results of student learning course material research method there is no interaction between the two methode tests with the use of methods of problem solving, but no effect of the use of methods of problem solving on critical thinking ability of students in results students learn the material Research Methods. Keywords: methods of problem solving, critical thinking, cognitive ability, research methods